2009
DOI: 10.1007/s10549-009-0311-7
|View full text |Cite
|
Sign up to set email alerts
|

An educational video to increase clinical trials enrollment among breast cancer patients

Abstract: Only 3% of women with breast cancer participate in cancer clinical trials nationwide. The lack of awareness about clinical trials is a significant barrier towards clinical trials participation. A study was conducted at a large urban Comprehensive Cancer Center to test (1) the effectiveness of an 18-min educational video on improving attitudes toward clinical trials and trials enrollment among new breast cancer patients seen at the Karmanos Cancer Institute, and (2) to assess racial differences in attitudes reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 23 publications
2
55
1
Order By: Relevance
“…Previous efforts to improve clinical trial enrollment have included interventions involving informational booklets and videos aimed at educating patients about the benefits and risks of clinical trials [38][39][40]. Others have tried to increase trial enrollment by improving the informed consent process [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous efforts to improve clinical trial enrollment have included interventions involving informational booklets and videos aimed at educating patients about the benefits and risks of clinical trials [38][39][40]. Others have tried to increase trial enrollment by improving the informed consent process [41].…”
Section: Discussionmentioning
confidence: 99%
“…Others have tried to increase trial enrollment by improving the informed consent process [41]. While these efforts improve patients' understanding of clinical trials, they have been largely unsuccessful at increasing clinical www.TheOncologist.com trial participation [39][40][41]. Studies involving minority-based community clinical oncology programs have shown promise as a way to facilitate clinical trial participation among racial minorities and other underserved populations [42].…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies directly evaluated this possibility; in both studies, the same 18-minute educational video served as the intervention. 7,8 One study found that among 126 patients with lung cancer who had not previously participated in a clinical trial, the video had a significant positive impact on likelihood of participating but not on attitudes. 8 The other study found that among 196 patients with breast cancer who had not previously participated in a clinical trial, the video had no significant effects on either outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies supported our findings. Two publications that focused on an educational video designed to increase clinical trial enrollment observed that the video did not significantly increase enrollment [23,24]. Similarly, cancer patients who did not understand chemotherapy were found to accept it for a small chance of clinical benefit, while doctors, who understood the therapy very well, were unwilling to do so [25].…”
Section: Discussionmentioning
confidence: 99%